ANALISIS KESALAHAN SISWA KELAS IV SD MENYELESAIKAN SOAL KPK DAN FPB BERDASARKAN PROSEDUR NEWMAN - Febriyanti, Dinda Seltina; Hamdani, Hamdani; Sabri, Tahmid (Universitas Tanjungpura, 2022)
AbstractThis study aims to analyze the types of errors and the factors that cause students to make mistakes in solving the LCM (Least Common Multiple) and GCD (Greatest Common Divisor) questions based on Newman's procedures in grade IV State Elementary School 01 Balai Karangan. The research method used in this research is descriptive qualitative. The research subjects in this study were the fourth grade students of State Elementary School 01 Balai Karangan, totaling 28 students. Data collection techniques in this study were tests and interviews. Based on the results of the study, the errors made by students were (1) misunderstood the question as much 55,36%, (2) transformation error as much 58,93%, (3) process skill error as much 83,04%, and (4) errors in writing the final answer as much 88,39%. While the factors that cause students to make mistakes are internal factors, namely from the lack of ability of the students themselves and external factors, namely from lack of attention, guidance, and motivation from teachers and families. Keyword: Error Analysis, Prosedur Newman, Error Type, Causative Factor, LCM and GCD.